Identifying senior high school students’ misconception on the momentum and impulse concepts uses three-tier diagnostic test - Nurul Sakinah; Irma Fitria Amalia; Rizal Adimayuda (Research in Physics Education, 2023)
The level of understanding of students' learning in studying physics material deserves attention so that things do not happen that are not in accordance with the realm of concepts set by experts. The concept of physics is indeed fun to learn but it is enough to make students feel difficult when learning every material concept. The cause is the abstract concept of physics and its complicated mathematical calculations, especially in the matter of momentum and impulses. Although several studies state that misconceptions in studying physics concepts can be overcome, they do not last long and will definitely happen again. Therefore, this study aims to identify misconceptions among high school students regarding the concept of momentum and impulse. The research method used is descriptive quantitative. The participants in this study were 37 students who were obtained using a purposive sampling technique. The instrument used is the Three-tier diagnostic test which is formulated based on the indicators contained in the school curriculum used. The research data were obtained from the results of an analysis of the answers and patterns of students' answers on the three-tier diagnostic test items. The results of the study showed that it was identified that more than fifty percent of students had misconceptions.